Body composition data of grizzly bears in the Greater Yellowstone Ecosystem 2000-2020 ... - Van, Frank T; Haroldson, Mark A; Bjornlie, Daniel; Thompson, Daniel; Nicholson, Jeremy; Gunther, Kerry; Wilmot, Katharine; Karabensh, Bryn E; Costello, Cecily; Corradini, Andrea; Cagnacci, Francesca (U.S. Geological Survey, 2023)
Understanding evolutionary processes that drive population dynamics is critical in ecology. Measuring the performance-density relationship in long-lived mammalian species demands long-term data, limiting the ability to observe such mechanisms. We tested density-dependent (intrinsic) and density-independent (extrinsic) drivers of body composition of grizzly bears (Ursus arctos) in the Greater Yellowstone Ecosystem over two decades. ...